Numerical Study of Temperature and Air Velocity Distribution In Oil Filling Factory - Hernawan Novianto; Prabowo Prabowo (JMES The International Journal of Mechanical Engineering and Sciences, 2017)
This paper describes the use of CFD modeling to analyze the thermal comfort in the oil filling factory which has an area of 3000 m2.the need for this analysis comes from an uncomfortable condition that is felt by the workers of the factory. A 3D simulation using FLUENT software 6.3.26 conducted to analyze the temperature and velocity distribution in the plant room. The water is assumed as an incompressible ideal gas, steady flow, turbulence models used k-ε standard, the SIMPLE algorithm and second order upwind discretisation. Analysis was conducted on existing models and propose models, whereby on a model propose, the diffuser is installed above the workers with a height of 4,2 m above the floor, the velocity of supply air diffuser is varied from 1,5 m/s, 2 m/s, and 2,5 m/s. The simulation results show that the temperature distribution in the existing conditions in the range of about 34-36 ° C, this value exceeds the thermal comfort standards specified by ASHRAE. The simulation results show that the proposed model better temperature distribution, where the temperature is generated in the range of ASHRAE thermal comfort criteria, ranging from 24-26 °C, and the supply air velocity at the diffuser inlet of 1,5 m/s recommended for use in AHU system. For the 20 units of the diffuser with inlet velocity of 1,5 m / s, the mass flow rate that should be handled by a cooling device is 9 kg/s and require a cooling capacity of 0,128 MW. This is 58% more efficient than cooling the entire room factory.